IDENTIFIKASI SENYAWA METABOLIT SEKUNDER DAN UJI AKTIVITAS EKSTRAK ETANOL HERBA MENIRAN (Phyllanthus niruri L.) TERHADAP CANDIDA ALBICANS MENGGUNAKAN METODE DIFUSI CAKRAM - Anita Apriliana; Eko Kusumawati; Selvitawati Selvitawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
The aim of this research is to know the ability of meniran ethanol extract (Phyllanthus niruri L.) in inhibiting the growth of Candida albicans. The research design is an experimental study. The extract used was herbal meniran extract made by maceration using 70% ethanol solvent, the content of ethanol extract of meniran tested against Candida albicans using disc diffusion method were 5%, 10%, 20%, 30% and 40%. Activity test conducted on Sabaraound Dextrose agar media that has been smeared with Candida albicans culture which has been standardized with Mc Farland standard. The pre-tested disc paper is first dipped into the extract with various concentrations. Incubated at 30 ° C for 24 hours and the inhibit zone formed was measured. The result showed that herbal ethanol extract of meniran resulted in drag zone diameter at Candida albicans ie 8,5 mm; 10.3 mm; 12.6 mm; 14.1 mm and 14.3 mm, for negative control 0 mm and positive control 20.1 mm. Data obtained from the results of the study were analyzed using one way anova method showed p - value <0,05, it was concluded that there was significant difference between negative control, 5%, 10%, 20%, 30%, 40% and positive control.